Polish translation and cross-cultural adaptation of the Caregiver Priorities and Child Health Index of Life with Disabilities questionnaire - Ewa Matuszczak; Justyna Zielinska-Turek; Wojciech Debek; Marta Diana Komarowska; Katarzyna Muszyńska-Rosłan; Jerzy Andrzej Wojnar; Adam Hermanowicz (Kazimierz Wielki University, 2017)
The aim of this study was to translate and adapt the Caregiver Priorities and Child Health Index of Life with Disabilities (CPCHILD) questionnaire into the Polish language, and to test the reliability and validity of CPCHILD scores of children with cerebral palsy (CP). Methods: This study consisted of two parts: the translation and  transcultural adaptation of the English version of the CPCHILD into Polish language and the validity testing of the Polish version of the CPCHILD. Patients: Parents of non-ambulatory children with CP aged between 5 and 18 years. All of the 25 children with cerebral palsy were classified using the Gross Motor Function Classification System as level V. Results: The Polish version of CPCHILD yielded similar test-retest reliability and score distributions across the GMFCS level as the original version. The best correlations were observed for domains that are close to the functional deficits. Conclusion: This study shows that the Polish version of CPCHILD, the same as English version, is a disease specific measure of the caregivers' perspective, is reliable and internally consistent, and can be reliably used to evaluate the health-related quality of life in Polish patients with CP from the caregivers' perspective.